ARTYKUŁ PRZEGLĄDOWY/REVIEW PAPERDiagnostics of neuropsychiatric complications in vascular diseases in the course of systemic connective tissue diseases - Fiedorowicz-Fabrycy, Irena; Brzosko, Marek (Reumatologia/Rheumatology, 2005)
Neuropsychiatric complications of systemic connective tissue diseases are currently the subject of interest of neurologists and rheumatolgists. Since the time that the new neuroimaging technics and serological and cerebrospinal fluid immunological testing have been introduced into neurological diagnostics such complications are described more commonly. Neuropsychiatric complications occur in 30-80% of patients with systemic connective tissue diseases. They result from the involvement of cerebrum, cerebellum, spinal cord and peripheral nervous system. Neuropsychiatric complications can be divided into primary and secondary ones that are the side effects of the treatment, metabolic disturbances and superimposing infections. Central nervous system complications may reflect the diffuse or focal damage to the nervous tissue or they may present as psychiatric symptoms. The neuroimaging diagnostics involves computed tomography, magnetic resonance imaging, single photon emission computed tomography and positron emission tomography. Ultrasonographic examinations could be also recommended as they are non-invasive, easy to repeat and accessible for severely ill people.